The effect of education on in-prison conflict: evidence from Argentina - Catherine Rodríguez
Using census data for Argentine prisons for the period 2002-2005, this paperpresents evidence of the positive e¤ect that prisoner education programs (pri-mary and some part of secondary schooling) have on in prison conflictivitymeasured as sanctions or violent behavior of the prisoner. In order to over-come the problems of endogeneity that education decisions generate we usean instrumental variables approach. Our results show a decrease in partici-pation in violent conflicts and bad behavior which can be partially attributedto education.prison based education, violent behavior